Prescription for health - Medical Video Library ([S.l.] : Medical Video Library, 1989)
Informative, interesting video programs, designed to improve the critical communication between health care professionals and their patients
Neurology series ; 50067 stroke : definition (v.1), 50068 stroke : treatment (v.2)
Keywords: Health; Neurology; Delivery of health care; Cerebrovascular Accident